Understanding prejudice and discrimination - Plous, Scott (McGraw-Hill, 2003)
This anthology, edited by Scott Plous, is designed as a supplementary text for a course in prejudice and discrimination. It represents a collection of readings edited, adapted, or revised specifically for this anthology - several of which have never been published before. The surveys, experiments, and other studies included are set in a cultural and historic context that includes personal narratives, news stories, legal decisions, poetry, social commentary, and assorted other material. Several readings come from people on the receiving end of prejudice (often referred to as "targets" of prejudice.) Interdisciplinary in its selection of readings, this anthology is an unusual combination of readings in which laboratory studies and national opinion polls appear side-by-side with U.S. Supreme Court decisions and New York Times articles